Agnes Macphail and Canadian Working Women - Crowley, Terry (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1991)
Abstract Women's involvement in broadening the activities of the Canadian state during the first half of the 20th century is examined in this study of the career of Agnes Macphail as it related to her efforts on behalf of working women. Noting her evolution from agrarian radical to social democrat, it stresses that Macphail's feminism stemmed from her beliefs in human rights, especially the need for greater equality of condition. As the first woman member of Parliament and of the Ontario legislature during 1921-51, Macphail's thought and activities were directed toward representing women's concerns, particularly those labouring on farms and in factories and offices, but they involved crucial personal decisions about motherhood as opposed to pursuing a career. Macphail helped to create the first universal federal social assistance program, contributed to the founding of the CCF, promoted union activity, and championed the first pay-equity legislation in Canada. She believed that integrationist politics offered the best route to assert women's influence on government.